Green manures for highland paddy in a mountainous area - Utumporn Chaiwong (2018)
An evaluation of opportunity to improve productivity of highland paddy with green manure was conducted as a participatory research in collaboration with farmers of Tee Cha village, Sop Moei sub-district, Mae Hong Son province in northern Thailand. Four species of legumes (Lablab purpureus, Vigna umbellata, Canavalia ensiformis and Mimosa invisa inermis) were grown before the farmer-managed rice crop (cv. RD21) in farmer's highland paddy field. The biomass and nutrient contents of the legumes and rice yield and yield component were evaluated. Rice yield in the farmer's field was increased for 16-44% after green manuring, depending on the legume species, with V. umbellata having the highest effect on rice yield, followed by C. ensiformis. Farmers evaluation of the green manure legumes agreed with measurement of nitrogen content of the legumes and subsequent rice yield. The experiment and participatory results suggest that there is an opportunity to improve rice yield in highland paddy with green manuring.